Sedimentology and sequence stratigraphy of the Middle–Upper Jurassic Krossfjord and Fensfjord formations, Troll Field, northern North Sea - Holgate,NE; Jackson,CA-L; Hampson,GJ; Dreyer,T (Petroleum Geoscience, 2013)
The Middle–Upper Jurassic Krossfjord and Fensfjord formations are secondary reservoir targets in the super-giant Troll oil and gas field, Horda Platform, offshore Norway. The formations comprise sandstones ( c . 195 m thick) sourced from the Norwegian mainland to the east, that pinch out basinwards into offshore shales of the Heather Formation to the west. Sedimentological analysis of cores from the Troll Field has identified six facies associations, which represent wave- and tide-dominated deltaic, shoreline and shelf depositional environments. Resulting depositional models highlight the complex distribution of depositional environments, and reflect spatial and temporal variations in physical processes at the shoreline, rate of sediment supply and accommodation development. These models are further complicated by the absence of coastal plain facies, which implies that the Troll Field was fully subaqueous during deposition, that shoreline regression was forced by falling sea level or that coastal plain deposits were removed by transgression. Genetic sequences bounded by major flooding surfaces (‘series’) exhibit laterally uniform thicknesses, implying no major tectonic influence on sedimentation. The recognition of pronounced variability in facies character and stratigraphical architecture emphasize the need for a robust depositional model of the formations in order to drive future exploration in these, and coeval, reservoirs.